Kinetics enhancement of lithium–sulfur batteries by interlinked hollow MoO2 sphere/nitrogen-doped graphene composite. Issue 48 (5th December 2017) - Wu, Xian; Du, Ying; Wang, Pengxiang; Fan, Lishuang; Cheng, Junhan; Wang, Maoxu; Qiu, Yue; Guan, Bin; Wu, Hexian; Zhang, Naiqing; Sun, Kening
Abstract : This communication reports an interlinked MoO2 and N-rGO composite as sulfur host for high-performance lithium sulfur battery. Abstract : The shuttle effect and poor redox kinetics are vital issues restricting the evolution of lithium sulfur batteries; it is therefore exigent to rationally design an effective sulfur host. Hence, this paper reports a hollow MoO2 sphere anchored on nitrogen-doped graphene. The hollow MoO2 sphere controls the polysulfide dissolution, and the nitrogen-doped graphene provides a conductive network and high sulfur loading. Meanwhile, the C–O–Mo bond interlinking MoO2 and N-doped graphene provides a pathway for electron transfer, and the synergistic effect enhances the kinetics of lithium sulfur batteries profitably. Ascribed to the unique structure of MoO2 /nitrogen-doped graphene, the obtained electrode exhibits a substantially enhanced electrochemical performance.